Determining the Efficacy of Providing Ice Compression for Fitness Enhancement After Speed Endurance Exercise on Reducing Heart Rate, IL-6, and Fatigue Index in Football Athletes - Muhammad Kharis Fajar; Agus Hariyanto; Endang Sri Wahjuni; Dwi Cahyo Kartiko; Gigih Siantoro; Yanyong Phanpheng; I Dewa Made Aryananda Wijaya Kusuma; Bayu Agung Pramono; Afif Rusdiawan; Adi Pranoto (Physical Education Theory and Methodology)
Objectives. This study aimed to investigate the effects of Ice Compression For Fitness (ICEFIT) on reducing heart rate, Interleukin-6 (IL-6) levels, and fatigue index in soccer athletes after performing speed endurance training.